Proposed mechanism of antibacterial mode of action of Caesalpinia bonducella seed oil against food-borne pathogens (Bangladesh Journal of Pharmacology, 2016)
The antibacterial mechanism of action of Caesalpinia bonducella seed oil on membrane permeability of Listeria monocytogenes NCIM 24563 (MIC: 2 mg/mL) and Escherichia coli ATCC 25922 (MIC: 4 mg/mL) was determined by measuring the extracellular ATP concentration, release of 260-nm absorbing materials, leakage of potassium ions and measurement of relative electrical conductivity of the bacterial cells treated at MIC concentration. Its mode of action on membrane integrity was confirmed by release of extracellular ATP (1.42 and 1.33 pg/mL), loss of 260-nm absorbing materials (4.36 and 4.19 optical density), leakage of potassium ions (950 and 1000 mmol/L) and increase in relative electrical conductivity (12.6 and 10.5%) against food-borne pathogenic bacteria L. monocytogenes and E. coli, respectively. These findings propose that C. bonducella oil compromised its mode of action on membrane integrity, suggesting its enormous food and pharmacological potential.